No Development of Imipenem Resistance in Pneumonia Caused by Escherichia coli. Issue 25 (June 2015) - Yayan, Josef; Ghebremedhin, Beniam; Rasche, Kurt; Callens., Steven
<x xml:space="preserve">Abstract</x> Background: Antibiotic resistance continues to rise due to the increased number of antibiotic prescriptions and is now a major threat to public health. In particular, there is an increase in antibiotic resistance to Escherichia coli according to the latest reports. Trial Design: This article examines, retrospectively, antibiotic resistance in patients with community- and nosocomial-acquired pneumonia caused by E coli. Methods: The data of all patients with community- and nosocomial-acquired pneumonia caused by E coli were collected from the hospital charts at the HELIOS Clinic, Witten/Herdecke University, Wuppertal, Germany, within the study period 2004 to 2014. An antibiogram was performed for the study patients with pneumonia caused by E coli. Antimicrobial susceptibility testing was performed for the different antibiotics that have been consistently used in the treatment of patients with pneumonia caused by E coli. All demographic, clinical, and laboratory data of all of the patients with pneumonia caused by E coli were collected from the patients' records. Results: During the study period of January 1, 2004 to August 12, 2014, 135 patients were identified with community- and nosocomial-acquired pneumonia affected by E coli. These patients had a mean age of 72.5 ± 11.6 (92 [68.1%, 95% CI 60.2%–76.0%] males and 43 [31.9%, 95% CI 24.0%–39.8%] females). E coli had a high resistance rate to ampicillin (60.7%), piperacillin (56.3%), ampicillin–sulbactam (44.4%), and co-trimoxazole (25.9%). No patients with pneumonia caused by E coli showed resistance to imipenem (P < 0.0001). Conclusion: E coli was resistant to many of the typically used antibiotics. No resistance was detected toward imipenem in patients with pneumonia caused by E coli.